Enhancing teacher competence in identifying student needs through NIMID at inclusive schools - Dudi Gunawan; Yoga Budhi Santoso; Prinanda Gustarina Ridwan; Hendriano Meggy; J. Juhanaini; Nandi Warnandi; Nazwa Laila Putri; Wanda Dwi Rahayu; Elvina Sabriyati (Inovasi Kurikulum)
Inclusive education prepares students to become global citizens who understand cultural, linguistic, and perspective diversity. This is in line with the principle of human rights, which affirms every individual's right to receive a decent education without discrimination. Inclusive education ensures that no student is neglected in the learning process. Competent teachers can create a compelling and quality learning environment. Need Identification Method Inclusive Design (NIMID) training is one way to improve understanding of inclusive education and teacher skills in designing inclusive learning programs. This study aims to measure the effectiveness of Needs Identification Method Inclusion Design (NIMID) training in improving teacher understanding. The experimental design method with a one-group pretest-posttest design was chosen to measure teacher understanding and skills. Non-parametric statistical tests with the Wilcoxon Signed-Rank Test were conducted to analyze the pretest-posttest results. The results showed that NIMID training improved teacher skills in the concept of inclusive education, identification, and assessment, and it was able to develop learning programs tailored to student's needs so that learning was optimal.